ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) RISK AND FIRM VALUE: A BIBLIOMETRIC ANALYSIS OF RESEARCH PATTERNS - Andayani Wuryan; Indrayani Indrayani; Iqbal Lhutfi; Maharani Wuryantoro; Haddy Mboob (RADJA PUBLIKA, 2025)
This study aims to map trends and research patterns regarding the relationship between Environmental, Social, and Governance (ESG) risk and firm value through a bibliometric approach. Although the concept of ESG is increasingly widely adopted in global business and investment practices, the results of academic research related to its impact on corporate value still show inconsistencies. Some studies have found that ESG is able to improve reputation, reduce risk, and strengthen company value, while others show negative impacts due to increased costs or misalignment of strategies. To answer this uncertainty, this study uses a data-based bibliometric analysis method from Scopus, with a total of 153 articles selected based on certain exclusion criteria in the period 2016–2025. Visualization and analysis were carried out using VOSviewer and RStudio software, and supported by a systematic literature review. The results of the analysis show a significant increase in the number of ESG publications since 2020, with contributions dominating from countries such as India, the United States, and China. In addition, there are five main thematic clusters in ESG research: governance and risk, corporate social responsibility (CSR), corporate value and performance, strategy and competitiveness, and theoretical perspectives. This study makes an important contribution in explaining the scientific landscape of ESG and firm value, as well as identifying research gaps that can be the basis for further research. These findings are relevant not only to academics, but also to investors, corporate managers, and policymakers who want to understand the strategic implications of ESG on corporate value.